The Principle of Intergenerational Justice in Environmental Management and Its Relation to the Concept of Sustainable Development - Sugirman, Andi (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The principle of intergenerational justice and its relationship to the concept of sustainable development in environmental management is an endlessly discussed issue. Considering that the environment is one of the most crucial elements for the survival on Earth, this study constructs the principle of intergenerational justice as an effort towards sustainable development in environmental management, as stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management. This study falls under the category of literature research, examining literature data from law books, journals, legislation, and other relevant references. The research findings indicate that the management and utilization of natural resources between generations should be carried out fairly, meaning that the present generation has an obligation to pass on the environment in a good condition to future generations. Therefore, environmental management and utilization must be based on moral and sustainability principles. The concept of sustainable development embodies the principles of intergenerational justice. In the practice of law enforcement, the principle of intergenerational justice has been implemented by the Philippine government, as exemplified by the Minor Oposa case in 1993, which involved deforestation. In Indonesia itself, the normative principles of intergenerational justice have been accommodated in various principles, as stated in Article 2 of Law Number 32 of 2009 concerning Environmental Protection and Management.